Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Mother trees, altruistic fungi, and the perils of plant personification - David G. Robinson; Christian Ammer; Andrea Polle; Jürgen Bauhus; Roni Aloni; Peter Annighöfer; Tobias I. Baskin; Michael R. Blatt; Andreas Bolte; Harald Bugmann; Jerry D. Cohen; Peter J. Davies; et al. (Trends in Plant Science, 2024)

Temporal shifts in the functional composition of Andean forests at different elevations are driven by climate change - Johanna Andrea Martínez‐Villa; Sandra M. Durán; Brian J. Enquist; Alvaro Duque; Christian Messier; Alain Paquette (Global Ecology and Biogeography, 2024)
Aim Andean forests are a global biodiversity hotspot. They harbour many species living within narrow climate ranges and a high functional diversity of trees. It remains still unclear how such hotspots respond to climatic changes over time. We investigated whether Andean forests are changing their functional composition over time along an elevational gradient by assessing changes in species composition, abundance and functional traits. Location An elevational gradient in Colombia's northern Andes. Time Period Species composition changes were studied two to four times from 2006 to 2017, and functional composition from 2016 to 2017. Major Taxa Studied A total of 1104 tropical tree species with in situ traits characterization. Methods We used seven morphological leaf traits and wood density values to analyse the functional trait dynamic over 10 years along an elevational gradient. By analysing changes in species composition, abundance and trait representation, we inferred the magnitude and direction of changes in functional composition. Then, we assessed if the functional change was related to climate change and demography. Results With increased minimum temperature and vapour‐pressure deficit, we found a decrease over time in mean values for leaf area and specific leaf area and increases in leaf thickness and leaf dry matter content. Long‐term temperature increases are smaller with increasing elevation, but the magnitude of trait changes is greater than in lowlands. Main Conclusions The functional composition is changing towards more conservative strategies over time across the elevation gradient, with the strongest changes observed at the highest elevations. This pattern is explained by the change in species turnover within communities due to higher recruitment rates of species with high leaf dry matter content values and low leaf area values. These shifts may be related to communities' responses to higher evapotranspiration demand and thermal stress, mainly at higher elevations.

Forestry in the Face of Global Change: Results of a Global Survey of Professionals - Austin Himes; Jürgen Bauhus; Shankar Adhikari; Saroj Kanta Barik; Hugh Brown; Andreas Brunner; Philip J. Burton; Lluís Coll; Anthony W. D’Amato; Jurij Diaci; Yonten Dorji; Ernest G. Foli; et al. (Current Forestry Reports, 2023)
Purpose of Review Forests support most global terrestrial biodiversity and contribute to the livelihood of billions of people, but these and other benefits are in jeopardy due to global change. This leads to questions, such as how to address the challenges of global change in forest management, given the lack of knowledge and deep uncertainty about future developments. In addition, many of the impediments to implement adaptation strategies are unknown. Recent Findings Here, we present an overview of results from a global survey of 754 forestry professionals (370 researchers and educators, 227 practicing foresters, 37 policymakers, 64 administrators, and 56 with other or unspecified roles) from 61 countries across 6 continents who were interested in global change issues. These professionals were asked about their opinion regarding three different adaptation strategies: resist , adapt , and transform . Most respondents agreed that the majority of global change factors will negatively influence the ability of forests to provide desired ecosystem services. Similarly, they agreed about major challenges when implementing adaptation strategies and specifically whether our current knowledge base is sufficient. These concerns were not limited to ecological aspects, but respondents also highlighted the need for a better appreciation of social/political and economic barriers, especially regarding transformation strategies. In addition, the response patterns, including differences due to economic status, highlight the importance of developing and evaluating adaptation strategies in a local social–ecological context. Summary Our study demonstrates a widespread perception on the part of forestry professionals around the world, especially among researchers and practitioners, that many global change factors will affect sustainable forest management negatively, resulting in the need for active silvicultural adaption. The results also suggest potential barriers to different adaptation strategies, particularly a relative lack of information and social acceptance for transform strategies. Further, this study highlights the importance of social and political factors and the need to understand the general public’s values regarding adaptation strategies as well as how the influence of public opinion is perceived by forest managers.

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)

Managing for the unexpected: Building resilient forest landscapes to cope with global change - Marco Mina; Christian Messier; Matthew J. Duveneck; Marie‐Josée Fortin; Núria Aquilué (Global Change Biology, 2022)
Natural disturbances exacerbated by novel climate regimes are increasing worldwide, threatening the ability of forest ecosystems to mitigate global warming through carbon sequestration and to provide other key ecosystem services. One way to cope with unknown disturbance events is to promote the ecological resilience of the forest by increasing both functional trait and structural diversity and by fostering functional connectivity of the landscape to ensure a rapid and efficient self‐reorganization of the system. We investigated how expected and unexpected variations in climate and biotic disturbances affect ecological resilience and carbon storage in a forested region in southeastern Canada. Using a process‐based forest landscape model (LANDIS‐II), we simulated ecosystem responses to climate change and insect outbreaks under different forest policy scenarios—including a novel approach based on functional diversification and network analysis—and tested how the potentially most damaging insect pests interact with changes in forest composition and structure due to changing climate and management. We found that climate warming, lengthening the vegetation season, will increase forest productivity and carbon storage, but unexpected impacts of drought and insect outbreaks will drastically reduce such variables. Generalist, non‐native insects feeding on hardwood are the most damaging biotic agents for our region, and their monitoring and early detection should be a priority for forest authorities. Higher forest diversity driven by climate‐smart management and fostered by climate change that promotes warm‐adapted species, might increase disturbance severity. However, alternative forest policy scenarios led to a higher functional and structural diversity as well as functional connectivity—and thus to higher ecological resilience—than conventional management. Our results demonstrate that adopting a landscape‐scale perspective by planning interventions strategically in space and adopting a functional trait approach to diversify forests is promising for enhancing ecological resilience under unexpected global change stressors.

Tree diversity effects on soil microbial biomass and respiration are context dependent across forest diversity experiments - Simone Cesarz; Dylan Craven; Harald Auge; Helge Bruelheide; Bastien Castagneyrol; Jessica Gutknecht; Andy Hector; Hervé Jactel; Julia Koricheva; Christian Messier; Bart Muys; Michael J. O’Brien; et al. (Global Ecology and Biogeography, 2022)
Aim Soil microorganisms are essential for the functioning of terrestrial ecosystems. Although soil microbial communities and functions are linked to tree species composition and diversity, there has been no comprehensive study of the generality or context dependence of these relationships. Here, we examine tree diversity–soil microbial biomass and respiration relationships across environmental gradients using a global network of tree diversity experiments. Location Boreal, temperate, subtropical and tropical forests. Time period 2013. Major taxa studied Soil microorganisms. Methods Soil samples collected from 11 tree diversity experiments were used to measure microbial respiration, biomass and respiratory quotient using the substrate‐induced respiration method. All samples were measured using the same analytical device, method and procedure to reduce measurement bias. We used linear mixed‐effects models and principal components analysis (PCA) to examine the effects of tree diversity (taxonomic and phylogenetic), environmental conditions and interactions on soil microbial properties. Results Abiotic drivers, mainly soil water content, but also soil carbon and soil pH, significantly increased soil microbial biomass and respiration. High soil water content reduced the importance of other abiotic drivers. Tree diversity had no effect on the soil microbial properties, but interactions with phylogenetic diversity indicated that the effects of diversity were context dependent and stronger in drier soils. Similar results were found for soil carbon and soil pH. Main conclusions Our results indicate the importance of abiotic variables, especially soil water content, for maintaining high levels of soil microbial functions and modulating the effects of other environmental drivers. Planting tree species with diverse water‐use strategies and structurally complex canopies and high leaf area might be crucial for maintaining high soil microbial biomass and respiration. Given that greater phylogenetic distance alleviated unfavourable soil water conditions, reforestation efforts that account for traits improving soil water content or select more phylogenetically distant species might assist in increasing soil microbial functions.

Enhanced light interception and light use efficiency explain overyielding in young tree communities - Laura J. Williams; Ethan E. Butler; Jeannine Cavender‐Bares; Artur Stefanski; Karen E. Rice; Christian Messier; Alain Paquette; Peter B. Reich (Ecology Letters, 2021)
Diverse plant communities are often more productive than mono‐specific ones. Several possible mechanisms underlie this phenomenon but their relative importance remains unknown. Here we investigated whether light interception alone or in combination with light use efficiency (LUE) of dominant and subordinate species explained greater productivity of mixtures relative to monocultures (i.e. overyielding) in 108 young experimental tree communities. We found mixed‐species communities that intercepted more light than their corresponding monocultures had 84% probability of overyielding. Enhanced LUE, which arose via several pathways, also mattered: the probability of overyielding was 71% when, in a mixture, species with higher ‘inherent’ LUE (i.e. LUE in monoculture) intercepted more light than species with lower LUE; 94% when dominant species increased their LUE in mixture; and 79% when subordinate species increased their LUE. Our results suggest that greater light interception and greater LUE, generated by inter and intraspecific variation, together drive overyielding in mixed‐species forests.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Ectomycorrhizal fungal diversity and saprotrophic fungal diversity are linked to different tree community attributes in a field‐based tree experiment - Nhu H. Nguyen; Laura J. Williams; John B. Vincent; Artur Stefanski; Jeannine Cavender‐Bares; Christian Messier; Alain Paquette; Dominique Gravel; Peter B. Reich; Peter G. Kennedy (Molecular Ecology, 2016)
Exploring the link between above‐ and belowground biodiversity has been a major theme of recent ecological research, due in large part to the increasingly well‐recognized role that soil microorganisms play in driving plant community processes. In this study, we utilized a field‐based tree experiment in Minnesota, USA , to assess the effect of changes in plant species richness and phylogenetic diversity on the richness and composition of both ectomycorrhizal and saprotrophic fungal communities. We found that ectomycorrhizal fungal species richness was significantly positively influenced by increasing plant phylogenetic diversity, while saprotrophic fungal species richness was significantly affected by plant leaf nitrogen content, specific root length and standing biomass. The increasing ectomycorrhizal fungal richness associated with increasing plant phylogenetic diversity was driven by the combined presence of ectomycorrhizal fungal specialists in plots with both gymnosperm and angiosperm hosts. Although the species composition of both the ectomycorrhizal and saprotrophic fungal communities changed significantly in response to changes in plant species composition, the effect was much greater for ectomycorrhizal fungi. In addition, ectomycorrhizal but not saprotrophic fungal species composition was significantly influenced by both plant phylum (angiosperm, gymnosperm, both) and origin (Europe, America, both). The phylum effect was caused by differences in ectomycorrhizal fungal community composition, while the origin effect was attributable to differences in community heterogeneity. Taken together, this study emphasizes that plant‐associated effects on soil fungal communities are largely guild‐specific and provides a mechanistic basis for the positive link between plant phylogenetic diversity and ectomycorrhizal fungal richness.

Functional identity is the main driver of diversity effects in young tree communities - Cornelia M. Tobner; Alain Paquette; Dominique Gravel; Peter B. Reich; Laura J. Williams; Christian Messier (Ecology Letters, 2016)
Two main effects are proposed to explain biodiversity–ecosystem functioning relationships: niche complementarity and selection effects. Both can be functionally defined using the functional diversity ( FD ) and functional identity ( FI ) of the community respectively. Herein, we present results from the first tree diversity experiment that separated the effect of selection from that of complementarity by varying community composition in high‐density plots along a gradient of FD , independent of species richness and testing for the effects of FD and community weighted means of traits (a proxy for FI ) on stem biomass increment (a proxy for productivity). After 4 years of growth, most mixtures did not differ in productivity from the averages of their respective monocultures, but some did overyield significantly. Those positive diversity effects resulted mostly from selection effects, primarily driven by fast‐growing deciduous species and associated traits. Net diversity effect did not increase with time over 4 years.

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Effects of Urbanization on Tree Species Functional Diversity in Eastern North America - Charles A. Nock; Alain Paquette; Matt Follett; David J. Nowak; Christian Messier (Ecosystems, 2013)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

How do traits vary across ecological scales? A case for trait‐based ecology - Julie Messier; Brian J. McGill; Martin J. Lechowicz (Ecology Letters, 2010)
Ecology Letters (2010) 13: 838–848 Abstract Despite the increasing importance of functional traits for the study of plant ecology, we do not know how variation in a given trait changes across ecological scales, which prevents us from assessing potential scale‐dependent aspects of trait variation. To address this deficiency, we partitioned the variance in two key functional traits (leaf mass area and leaf dry matter content) across six nested ecological scales (site, plot, species, tree, strata and leaf) in lowland tropical rainforests. In both traits, the plot level shows virtually no variance despite high species turnover among plots and the size of within‐species variation (leaf + strata + tree) is comparable with that of species level variation. The lack of variance at the plot level brings substantial support to the idea that trait‐based environmental filtering plays a central role in plant community assembly. These results and the finding that the amount of within‐species variation is comparable with interspecific variation support a shift of focus from species‐based to trait‐based ecology.

Suspension of Multi-Walled Carbon Nanotubes (CNTs) in Freshwaters: Examining the Effect of CNT Size - Nelson J. O’Driscoll; Tammy Messier; Michael D. Robertson; John Murimboh (Water, Air, & Soil Pollution, 2010)

Arm?trunk coordination in the absence of proprioception - E. Tunik; H. Poizner; M. F. Levin; S. V. Adamovich; J. Messier; Y. Lamarre; A. G. Feldman (Experimental Brain Research, 2003)

Hierarchical habitat selection by barren-ground grizzly bears in the central Canadian Arctic - Philip D. McLoughlin; Ray L. Case; Robert J. Gau; Dean H. Cluff; Robert Mulders; François Messier (Oecologia, 2002)

Spatial and temporal distribution of chloroplast DNA polymorphism in a tropical tree species - H. Caron; S. Dumas; G. Marque; C. Messier; E. Bandou; R. J. Petit; A. Kremer (Molecular Ecology, 2000)
The level and the spatial organization of chloroplast DNA polymorphism were investigated in Dicorynia guianensis Hamshoff (Caesalpiniaceae) at different spatial and temporal scales. D. guianensis is a canopy tree of the rain forest that is distributed throughout the Guiana plateau in small aggregates. Twelve different haplotypes were identified using restriction analysis of polymerase chain reaction (PCR) amplified fragments of the chloroplast genome. When populations from different areas of French Guiana were compared, a clear geographical pattern of haplotype frequencies was identified along the Atlantic coast. This pattern is most likely the result of the restriction–expansion dynamics of the tropical forest during the Quaternary. At the local level, D. guianensis was characterized by a high level of within population diversity. Maintenance of within population diversity results from the dynamics of the aggregates; stochastic demography associated with the turnover of aggregates generates genetic differentiation among them. At the stand level, a strong spatial aggregation of haplotypes persisted from the adult to the seedling cohort indicating limited seed flow. There was also a strong difference in levels of diversity between the cohorts which suggested that recruitment over several years is needed in order to maintain genetic diversity during regeneration.

Comparison of variability of initial kinematics and endpoints of reaching movements - Julie Messier; J. F. Kalaska (Experimental Brain Research, 1999)